Permeability Characteristics of Tropical soils at UTP Campus - Che Wan Samsudin, Che Wan Muhsi (2010)
Soil permeability varies spatially and this spatial variability causes difficulty to representing a soil with a deterministic or precisely defined set of permeability value. In Malaysia, the studies on the spatial variability of soil permeability are limited. This study examines the spatial variability of soil permeability in UTP campus area located in Tronoh. The objective is to map the variation in soil hydraulic characteristics in the study area. Statistical and geostatistical method was used in this study. 50 soils sample were collected on the field from predefined geo-grid location. GPS (Global Positioning System) is used to determine the reference points for the making of the the geo-grid sampling locations. Samples were then taken to the laboratory for analysis. The method that used to measure the permeability of the soil samples was The Falling Head Permeability test. Laboratory test result were then subjected to statistical and geostatistical analysis. Digitizing Software was used to digitize the map of the study area. Geostatistical characterization was performed by the GS+ and Surfer Software. Kriging method is used for the interpolation of the ensample location and preparing map of the spatial variability of the permeability rates in UTP campus area is prepared. Besides, it also can allows mapping of the spatial distribution and the normal statistics will helped in identifying causes of the variability in the soil permeability. Others, even the semivariogram shows the consistent result, however the relatively low r2 (0.638) show poor fit to data. This is because in the fact that the number of the sample is not enough for that extend of area studied. The significant variation of soil permeability exists in the area of studied are shown in the result. Larger range and the lower sill indicates that the soil permeability are spatially dependent over long distance (large range) and the variability is low (indicates by low sill). Land disturbance and land topographic conditions donate to the variability of soil permeability.